Condicionamento fisiológico na germinação de sementes e vigor de plântulas de Samanea tubulosa (Bentham) Barneby e Grimes (Fabaceae) e Lonchocarpus sp. (Fabaceae) - Lima, Ana Paula Barbosa (2013)
Priming is a collection of techniques used to accelerate the germination process of seeds which presents slow germination and uninform like those of native forest species, as well as improved quality seeds with low performance. The main goal of this project was to evaluate the priming effect on Samanea tubulosa and Lonchocarpus sp. seeds, in germination of seeds and seedling performance. After the determination of absorbing curve of each specie, the seeds were conditioned on polyethylene glycol 6000 (PEG 6000) solution to reach seed moisture of 20, 30, 40 and 50%, beyond the initial seed moisture. The primed seeds were underwent an immediate sowing, sowing after drying and sowing after drying and storage for 30 days in cold chamber. S. tubulosa seeds were sow on a paper roll and were put in a germination chamber BOD type at the temperature of 30o C to evaluate the speed and percentage of germination, height and dry matter mass of the topping part and root. Lonchocarpus sp. seeds. were sow in plastic boxes contending the mixture of sand with middle granulometry and vermiculite (1:1), and then put in a nursery with 50% of shadow in screen house. It was evaluated the speed and the percentage of emergency until its stabilization and the plants‟ stem height and diameter, in order to calculate the plant growing during the 30 and 90 days of sowing. By the last evaluation, the plants were removed from the handling substrate to measure the roots and the determination of dry matter massv and Dickson‟s quality index. The experiment was carried out in a randomized to S. tubulosa and in randomized blocks to Lonchocarpus sp., in a factorial arrangement 4x3+1 (four water content: 20, 30, 40 and 50%; three pre-seeding treatments: 1- priming, 2- priming and drying and 3- priming, drying and storing for 30 days) repeating four times. Priming increased the speed germination of S. tubulosa seeds. The percentage of seed germination and shoot height of seedlings 11 decreased as the water content of the seeds is high by conditioning. Furthermore, the seedling vigor S. tubulosa is undermined when the conditioned seeds are dried and stored. The conditioning seed Lonchocarpus sp. is not effective in increasing the rate and speed of emergence. When the seeds are subjected to drying and storage plant vigor is impaired. Why not be effective in raising the quality of seeds compared to the control, the conditioning is not recommended for seeds of S. tubulosa and Lonchocarpus sp.